The Effect of Additional Jobs Method on Developing Some Physical and Motor Abilities of Hand Reel For Students - Nizar Hussain Jafar Alnafakh; Afrah Hataf Allawi (Institute of Medico-legal Publications Pvt Ltd, 2021)
The research problem was that the handball game is one of the different activities and sports which aretaught in three stages of the faculties and departments of physical education and sports sciences, and in thethree stages, there is a set of skills required to be learned by the student as well as the students’ enjoymentof physical, kinetic and other psychological abilities. Additional duties as a method for teaching femalestudents has become necessary for female students in light of their limited capabilities, especially at thepresent time, as we have not learned that most of the female students in colleges and departments of PhysicalEducation and Sports Sciences come from a non-athletic environment, which makes it difficult for the taskof teaching staff in specific colleges and departments, and the objectives of the research were to identifyOn the effect of the style, additional duties in developing some physical and motor abilities for femalestudents, the research community consisted of students of the third stage of the Department of PhysicalEducation and Sports Sciences - College of Education for Girls / University of Kufa for the academic year(2020-2021) and of (35) students for this was determined a sample Research from that community by (20)students by random method (lottery) from the research community, and (10) students were selected for eachgroup, and the physical abilities were The mobility of the research is (the transitional velocity and the forcedistinguished by the speed and explosive power) and the conclusions were: The two additional duties and - apositive effect on the development of the physical and kinetic abilities under study for the handball students,and the two additional duties and - positive impact on the development of the psychological endurance ofthe handball students .